A road map for reliable power electronics for more electric aircraft - Wileman, A. J.; Aslam, Sohaib; Perinpanayagam, Suresh (Elsevier, 2021)
The gradual evolution from hydro-pneumatic to electrical disposition of power in aircraft has placed stringent requirements on the reliability of power electronic components in current and future aerospace applications. This paper examines the prevalent state-of-the-art in power electronics and provides an analytical overview of power electronics in More Electric Aircraft (MEA) vis-à-vis the generation and distribution of power within these aircraft. The types of power devices currently employed for multiple conversion topologies are analysed and weighed according to their respective reliability characteristics. Beginning with an in-depth review of failure modes in the currently available devices, the paper highlights the salient emerging state-of-the-art Wide Band Gap (WBG) technologies such as Gallium Nitride (GaN) and Silicon Carbide (SiC) and draws an extensive comparison with their Silicon counterparts. A comprehensive examination of techniques employed for the estimation of the reliability of WBG power devices has revealed a number of areas that merit due consideration. For instance, the physics-based models that have been developed to assess the operational lifetime of silicon-based devices for given failure modes require revamping in light of the new materials and the unique electrical and physical characteristics the WBG devices possess. Similarly, the condition monitoring techniques, with respect to the primary and secondary parameters, require further investigation to determine highly representative feature vectors that best describe the degradation within these devices. More significantly, optimisation of the proposed techniques for the health assessment of these devices needs to be pursued through the optimal use of vital parameters. Keeping these critical findings in perspective, a road map highlighting various avenues for power electronics optimisation in MEA is put forth to apprise the aerospace fraternity of its growing significance.
Keywords: More electric aircraft; Reliability; Power electronics; Wide bandgap devices